Greening monies: Three trajectories for the socio-environmental transformation - Barinaga, Ester (Zeitschrift für Theoretische Soziologie, 2026)
Money is central to capitalism and its sustainability crises. This article argues that it is not money itself, but its internal design and governance – how it is created, distributed, and governed – that drives inequality, ecological degradation, and unsustainable growth. Yet, money’s architecture is not fixed; it can be reimagined to foster fairer, greener economies. Approaching money as a socio-technical assemblage, the article first traces how conventional money creation – dominated by private banks – fuels environmental and social harm. It then examines three innovative monetary initiatives – Turuta, Vilawatt, and Plastic Bank – each redesigning money to align economic activity with ecological care. These initiatives embody distinct organizing principles: the commons (Turuta), the state (Vilawatt), and the market (Plastic Bank). By embedding environmental stewardship into monetary rules, they reshape individual agency and collective action, offering pathways toward a just and sustainable future. In rethinking money, these experiments open new horizons for civilizational change.